ISTILAH MENGUASAI TERHADAP UMKM DALAM HUBUNGAN KEMITRAAN DENGAN BENTUK INTI-PLASMA - Intan Purwanti; Anna Maria Tri Anggraini (Faculty of Law, Universitas Trisakti, 2023)
In the modern business landscape, large and small companies frequently form collaboration agreements with micro, small, and medium-sized enterprises (MSMEs), creating mutual benefits. This study investigates the interpretation of 'ownership' and/or 'control' of MSMEs as business partners in partnerships, examining the application of criteria in two KPPU decisions (Number 21/KPPU-K/2019 and Number 03/KPPU-K/2021). Using normative and descriptive research methods with primary and secondary data, the study finds that 'ownership' implies an unequal condition resulting in a loss for one party, while 'control' involves decision-taking. The decisions reveal instances of domination by large businesses over MSMEs, each with distinct criteria for control and/or ownership. The study recommends KPPU to formulate guidelines clarifying the terms 'owning' and/or 'controlling' concerning medium/large businesses towards MSMEs.